Risk factors for gastrointestinal bleeding in patients with gastrointestinal cancer using edoxaban. (12th September 2021) - Bosch, Floris T. M.; Mulder, Frits I.; Huisman, Menno V.; Zwicker, Jeffrey I.; Di Nisio, Marcello; Carrier, Marc; Segers, Annelise; Verhamme, Peter; Middeldorp, Saskia; Weitz, Jeffrey I.; Grosso, Michael A.; Duggal, Anil; et al.
Abstract: Background: In the Hokusai VTE Cancer study, the risk of major bleeding was 2.9% higher in the edoxaban group compared with the dalteparin group, mainly due to more gastrointestinal bleedings in patients with gastrointestinal cancer. The identification of risk factors for gastrointestinal bleeding may help to guide the use of DOACs in these patients. Objectives: To evaluate risk factors for gastrointestinal bleeding in patients with gastrointestinal cancer receiving edoxaban. Patients/Methods: In this nested case‐control study in patients with gastrointestinal cancer randomized to edoxaban in the Hokusai VTE Cancer study, cases (patients with clinically relevant gastrointestinal bleeding during treatment) were randomly matched to three controls (patients who had no gastrointestinal bleeding). Data for the 4‐week period prior to bleeding were retrospectively collected. Odds ratios (ORs) were calculated in a crude conditional logistic regression model and a multivariable model adjusted for age, sex, and cancer type. Results: Twenty‐four cases and 64 matched controls were included. In the multivariable analysis, advanced cancer, defined as regionally advanced or metastatic cancer (OR 3.6, 95% CI 1.01–12.6) and low hemoglobin levels (OR 4.8, 95% CI 1.5–16.0) were significantly associated with bleeding. There was no significant difference in patients with resected tumors (OR 0.4, 95% CI 0.1–1.4), or in patients on chemotherapy (OR 1.3, 95% CI 0.5–3.5). Conclusion: Advanced cancer and low hemoglobin levels were associated with an increased risk of gastrointestinal bleeding in patients with gastrointestinal cancer receiving edoxaban. We were unable to identify other risk factors, mainly due to limited statistical power.